Effect of Cyclopentolate on In Vivo Schlemm Canal Microarchitecture in Healthy Subjects. Issue 2 (February 2017) - Rosman, Michael S.; Skaat, Alon; Chien, Jason L.; Ghassibi, Mark P.; Sarimiye, Tarela F.; Ritch, Robert; Liebmann, Jeffrey M.; Park, Sung Chul
Abstract : Purpose: To characterize the in vivo effect of cyclopentolate on the microstructure of Schlemm canal (SC) in healthy eyes. Methods: For healthy subjects, 81 serial horizontal enhanced depth imaging optical coherence tomography B-scans (interval between scans, ∼35 μm) of the nasal corneoscleral limbal area were obtained before and 1 hour after cyclopentolate 1% administration in 1 eye. The structures of aqueous and blood vessels in each scan were used as landmarks to select 50 overlapping scans between the 2 sets of 81 serial scans (before and after cyclopentolate administration). The SC cross-sectional area was measured in each of the 50 selected scans. After 3-dimensional reconstruction, SC volume was determined. Results: Twelve eyes (12 healthy subjects) were imaged successfully before and after cyclopentolate administration. Mean age was 27.8±4.9 years (range, 25 to 38 y). Following cyclopentolate administration, mean intraocular pressure did not change significantly (13.9±1.5 to 14.2±1.5 mm Hg; P =0.19). Mean SC cross-sectional area decreased by 17%, from 3563±706 to 2959±460 μm 2 ( P <0.001). Mean SC volume in the overlapping area (approximately 1.7 mm of circumferential length of SC) decreased from 6, 164, 061±1, 220, 787 to 5, 119, 462±794, 763 μm 3 ( P <0.001). The decrease in the mean SC cross-sectional area after cyclopentolate administration was greater in eyes with larger baseline SC cross-sectional area ( P <0.001, R =0.873). Conclusions: Cyclopentolate causes a reduction in SC dimensions in healthy eyes. Future studies are warranted to determine the exact mechanism(s) of this change.